Immunohistochemical markers of the activity of apoptosis and proliferation in women with adenomyosis who had papillary thyroid carcinoma - M.D. Tronko; A.O. Danylova; L.V. Kalugina; N.V. Kosei; T.M. Kuchmenko; Y.M. Bondarenko (Publishing House TRILIST, 2023)
Research objectives: to evaluate the activity of apoptosis and proliferation mechanisms of eutopic endometrium in patients with adenomyosis who had a history of papillary thyroid carcinoma (PTC). Materials and methods. 63 women of reproductive age were examined: group I - 31 patients with adenomyosis and PTC in history, group II - 32 patients with adenomyosis and normal thyroid status. The intensity of pelvic pain was assessed using a visual analog scale in all women. The material for morphological research was obtained with Pipelle biopsy of the endometrium in the secretory phase of the menstrual cycle. A morphological study was performed on 30 biopsies of eutopic endometrium (15 samples from patients of group I and 15 samples from patients of group II). An immunohistochemical study was performed using monoclonal antibodies to cell-specific markers Bcl-2 (DAKO, clone 124) and Ki-67 (DAKO, clone MIB-1). Results. High expression of Bcl-2 was detected in the endometrial glandular epithelial cells (EGECs) in 70% and 62.5% of samples in group I and II respectively (р > 0.05), the number of Bcl-2-positive cells was significantly higher in samples from group I (80.0 ± 13.1% versus 60.0 ± 15.2% in group І and ІІ respectively, р < 0.05). In endometrial stromal cells (ESCs) high expression of Bcl-2 was detected in 90% and 100% of samples from group I and II respectively (р > 0.05), no significant difference in the number of positive cells was found between groups (18.9 ± 12.2% and 12.6 ± 9.1% in group І and ІІ respectively, р > 0.05). Expression of Ki-67 was detected in the EGECs in 70% and 62.5% (р > 0.05) of samples in group І and ІІ respectively and in the ESCs in 100% of samples from groups I and II respectively. The immunocytochemical Ki-67 labelling index was much more prominent in group I (45.0 ± 11.4% versus 25.8 ± 16.7% EGECs (р < 0.05); 26.5 ± 10.2% versus 16.3 ± 8.9% ESCs (р < 0.05) for group I and II respectively). Conclusions. Altered proliferation of the eutopic endometrium with marked resistance to apoptosis was found in reproductive aged female with adenomyosis and PTC in history, that is can be considered as a marker of the aggressiveness of the disease course in this cohort of patients.